Acidochromism of donor–acceptor Stenhouse adducts in organic solvent. Issue 80 (15th August 2022) - Fiorentino, Antonio; Sachini, Brian; Corra, Stefano; Credi, Alberto; Femoni, Cristina; Fraix, Aurore; Silvi, Serena
Abstract : First generation DASA derivatives can be reversibly isomerized upon protonation, thus behaving as acidochromic compounds in halogenated organic solvent. Abstract : First generation DASA derivatives can be reversibly isomerized from the coloured, open form to the colourless, closed isomer upon protonation, thus behaving as acidochromic compounds in halogenated organic solvent.